Continuity and discontinuity in the Czech legacy of the Vienna School of Art History - Milena Bartlová (Journal of Art Historiography, 2013)
This article considers the development of Czech art history from the late nineteenth century to the present. It argues that while Czech art historians were anxious to establish a distinctive art historical voice in Europe, they were led a symbiotic relationship with the Vienna School. Most of the leading art historians of the early years of the Czechosovak Republic after 1918 studied with Alois Riegl, Franz Wickhoff, Max Dvořák of Josef Strzygowski, and maintained a strong loyalty to the values and methods of their teachers. Thus for all that 1918 marked a political watershed, there was considerable continuity with the Vienna School of the Habsburg Empire. Despite the numerous subsequent political and ideological events, including four decades of Communist, Czech art historians continued to regard Vienna School art historians as fundamental points of reference, and this has been sustained by a self-understanding that has emphasised continuity with the past.